(untitled) (Progressive Agriculture, 2014)
The present study aimed at obtaining the existing grain storage facilities - their problems and prospects at farmers, commercial, common and co-operative levels on some selected flood prone areas of Bangladesh. The study was conducted at Belkuchi upazila under Sirajgonj district. A total of randomly selected forty farmers and ten traders were surveyed from four villages under four different unions through structured questionnaire. Farmers and traders were classified as small, medium and large on the basis of their total land ownership and annual income status. The farmers used traditional storage structures such as Dole, berh, Motka, Jala, steel drum, gunny and plastic bags and Gola. On the other hand, the traders used gunny and plastic bags and privately owned godowns for storing food grains for short time basis. Average production, consumption, sale, farm use, labour wage, storage volume, cost, durability and losses of different storage structures for major grain crops like paddy, wheat and mustard were identified by farmers and traders category. Considering the capital cost, expected life and storage loss steel drum, gunny and plastic bags and Motka/Jala were found more economical for the farmers. The advantages and disadvantages of farmers, commercial, common and co-operative level storage structures were also identified. As the study area was a flood prone one, average 60% farmers were affected and average 8% stored grains were damaged by the flood of 2007. A total of 73% farmers and traders expressed their interest on co-operative storage system at the time of flood to store food grains with paying cost as they have no alternative storage facilities other than the proposed safely constructed co-operative storage structures. On the basis of the opinion of farmers and traders, the suitable location and type of storage structure were also proposed. A layout design and the cost of an operational storage structure for storing 60 metric tonnes of paddy and the possible management of the co-operative storage system were also proposed. DOI: http://dx.doi.org/10.3329/pa.v18i2.18244 Progress. Agric. 18(2): 223 - 233, 2007